The Influence of Resilience, Job Embededness, and Workload on Employee Performance - Mujanah, Siti; Edden, Hatta Mayda Nur; Noranee, Shereen; Ahmad, Nursaadatun Nisak (Journal of Advances in Accounting, Economics, and Management, 2023)
This study analyzes the influence of resilience, job embeddedness, and workload on employee performance. Employing a quantitative approach with an explanatory design, primary data was collected through questionnaires from 60 permanent employees. Data analysis involved instrument quality tests (validity and reliability) and classical assumption tests (normality, multicollinearity, heteroscedasticity), followed by multiple linear regression analysis. The findings indicate that resilience, job embeddedness, and workload, both partially and simultaneously, have a positive and significant effect on employee performance. The constructed regression model explains 61.6% of the variation in employee performance. These findings underscore that developing psychological resilience, strengthening employee attachment to their jobs and the organization, and effectively managing workload are crucial factors in enhancing productivity and achieving company objectives in the construction sector.